2012
DOI: 10.1186/1478-4491-10-8
|View full text |Cite
|
Sign up to set email alerts
|

Emigration preferences and plans among medical students in Poland

Abstract: BackgroundMigration and ethical recruitment of health care workers is receiving increased attention worldwide. Europe’s aging population is creating new opportunities for medical doctors for finding employment in other countries, particularly those of a better standard of living.MethodsWe conducted a survey among 1214 medical students in five out of eleven universities in Poland with medical schools in October 2008. A series of statistical tests was applied to analyse the characteristics of potential migrants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 5 publications
7
27
2
5
Order By: Relevance
“…For instance, major reasons for leaving Lithuania were higher salary, better professional opportunities, and better quality of life [27], similarly to the findings among Czech physicians [28] and students from Poland [11]. …”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…For instance, major reasons for leaving Lithuania were higher salary, better professional opportunities, and better quality of life [27], similarly to the findings among Czech physicians [28] and students from Poland [11]. …”
Section: Discussionmentioning
confidence: 67%
“…The total percentage of students that are considering emigration (84.7%) is higher than in other Eastern European countries. For comparison, Polish students estimated the likelihood of emigration to be around 50% [11]. 60% of medical residents from Lithuania stated that they intended to emigrate, 15% of them permanently [27], and only 45% of the Czech physicians are contemplating emigration [28].…”
Section: Discussionmentioning
confidence: 99%
“…The surveys conducted revealed that the primary reasons for employment in Germany were easy access to specialist medical education, better labour conditions, and higher compensation. In a survey conducted in 2008 among 1214 students at five Polish universities, the same attracting factors were determined (Krajewski-Siuda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Of the Polish physicians working in Germany, the largest share, or around 70 per cent, worked in hospitals (BAEK, 2015). For Polish physicians, Germany represents an appealing and popular destination country (Krajewski-Siuda et al, 2012). Not only economic factors are reasons for the emigration to Germany, but also the geographic proximity to their homeland.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for the migration is low salaries, especially for young medical doctors and mid-level health personnel (Siyam and Dal Poz, 2014). These processes also affect medical students in Poland who see emigration as an important alternative to career development (Krajewski-Siuda et al, 2012). Thus, it intensifies the brain-drain phenomenon, which is particularly severe for the economy from the perspective of the availability of highly-skilled workers (Hejdukova and Kurekova, 2016;Krajewski-Siuda and Romianuk, 2007).…”
Section: Resultsmentioning
confidence: 99%